2019
DOI: 10.5005/jp-journals-10005-1703
|View full text |Cite
|
Sign up to set email alerts
|

Nanosilver Fluoride—A Paradigm Shift for Arrest in Dental Caries in Primary Teeth of Schoolchildren: A Randomized Controlled Clinical Trial

Abstract: Background: Due to limited financial resources, poor access to basic oral care, and the high cost of restorative treatment, children of low-income nations have their general health, social well-being, and education opportunities affected by untreated dental caries. Arresting caries treatment (ACT) has been proposed to manage untreated dental caries in children of disadvantaged communities. Aims and objectives: The purpose of the present controlled clinical trial is to investigate the effectiveness of a new ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…Moreover, AgNPs are capable of anchoring and penetrating the bacterial cell wall, causing structural changes to the cell membrane, such as cell membrane permeability and cell death. 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, AgNPs are capable of anchoring and penetrating the bacterial cell wall, causing structural changes to the cell membrane, such as cell membrane permeability and cell death. 24 …”
Section: Discussionmentioning
confidence: 99%
“…In this study, all patients used fluoridated toothpaste, and with the addition of the NS mouthwash, produced a significant effect in reducing WSLs as a result of the synergistic actions of the NS and fluoride combined. 24 …”
Section: Discussionmentioning
confidence: 99%
“…1 a). Silver nano particles were also validated using UV/Vis spectrophotometer (Thermo Electron- Evolution 300) to detect the UV/Vis absorption spectrum of the resulting solution [ 14 , 27 ] (Fig. 1 b).…”
Section: Methodsmentioning
confidence: 99%
“…Although data on NSF have shown promising results in arresting [ 12 , 14 ] and remineralizing pre-formed or pre-existing carious lesions [ 10 , 15 ], to the best of our knowledge, no published studies have investigated its effect on resisting demineralization of initially sound enamel in primary teeth. Therefore, the present in vitro study aimed to investigate the potential of experimental NSF formulation in prevention of demineralization of sound enamel compared to commercial 5% sodium fluoride varnish in primary teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple in vitro researches have investigated the antimicrobial effects of AgNPs on carious tooth structures and have confirmed the substantial antibacterial effect of NSF on Streptococcus mutans and Lactobacilli [12][13][14][15][16]. Additionally, several studies [10,17,18] have reported that NSF is effective in arresting active dentine caries without any distinctive tissue pigmentation.…”
Section: Introductionmentioning
confidence: 99%